Transmissible ST3-IncHI2 Plasmids Are Predominant Carriers of Diverse Complex IS26-Class 1 Integron Arrangements in Multidrug-Resistant Salmonella - Zhao, Hang; Chen, Wenyao; Xu, Xuebin; Zhou, Xiujuan; Shi, Chunlei (Frontiers in Microbiology, 2018)
Diverse mobile genetic elements (MGEs) including plasmids, insertion sequences and integrons play an important role in the occurrence and spread of multidrug resistance (MDR) in bacteria. It was found in previous studies that IS26 and class 1 integrons integrated on plasmids to speed the dissemination of antibiotic-resistance genes in Salmonella. It is aimed to figure out the patterns of specific genetic arrangements between IS26 and class 1 integrons located in plasmids in MDR Salmonella in this study. A total of 74 plasmid-harboring Salmonella isolates were screened for the presence of IS26 by PCR amplification, and 39 were IS26-positive. Among them, 37 isolates were resistant to at least one antibiotic. The thirty-seven antibiotic-resistant isolates were further involved in PCR detection of class 1 integrons and variable regions, and all were positive for class 1 integrons. Six IS26-class 1 integron arrangements with IS26 inserted into the upstream or downstream of class 1 integrons were characterized. Only 31 antibiotic-resistant isolates were positive for the six IS26-class 1 integron arrangements so as to display eight complex IS26-class 1 integron arrangement patterns. IncHI2 was dominant incompatibility group in this study, which all belonged to ST3 by plasmid double locus sequence typing. These 21 IncHI2-positive isolates harbored six complex IS26-class 1 integron arrangement patterns. After liquid conjugation, 19 transconjugants were obtained with the conjugation rate of 90.8%. Co-transfer of IncHI2 plasmids, MDR phenotypes as well as complex IS26-class 1 integron arrangements was observed in these transconjugants. Further S1-PFGE and Southern blot confirmed the existence of IncHI2 plasmids in these tranconjugants and the localization of four complex IS26-class 1 integron arrangements on corresponding IncHI2 plasmids. The conjugation frequency of IncHI2 plasmids transferring alone was 10-5 to 10-6, reflecting that different complex IS26-class 1 integron arrangement patterns didn’t significantly affect conjugation frequency (P>0.05). These data suggested that class 1 integrons represent the hot spot for IS26 insertion, forming diverse MDR loci. And ST3-IncHI2 was the major plasmid lineage contributing to the horizontal transfer of composite IS26-class 1 integron MDR elements in Salmonella.